Feasibility Of Manganese Sequestration By Genetically Modified Escherichia coli K-12 - Awang, Huda (2018)
Manganese, released by industries through wastewater, caused long term effect on human’s neurological functions. Application of chemical treatments will generate more waste sludge when cleaning the metal contaminant in diluted concentration. Thus, application of genetically modified Escherichia coli K-12 as a biosorbent was attempted to solve the problems. The objectives of this research were to study the feasibility of the techniques of preparing targeted DNA fragment, plasmid (pUC19) and host cells (E. coli K-12) for successful transformation, to develop a random genetic manipulation (genetically modified) for E. coli K-12 and to determine the effect of genetically modified E. coli K-12 in sequestering manganese. A DNA fragment had been isolated from Ceriporiopsis subvermispora FP105752, cloned into plasmid pUC19 and transformed into E. coli K-12. The transformed E. coli K-12 colonies were bigger in size with light orange colour. The modified DNAof E. coli K-12 was sequenced and analysed using Basic Local Alignment Search Tool (BLAST) to identify the cloned DNA fragment. The cloned DNA fragment was identified as Ascomycota sp. ARIZ RT Ash-1 internal transcribed spacer 1 with 82% of similarity indicating that random genetic manipulation towards E. coli K-12 was achieved. The genetically modified E. coli K-12 had been compared to the nongenetically modified E. coli K-12 by testing both strains in Luria Bertani media containing 200, 400, 600, 800 and 1 000 μM of MnSO4. The genetically modified E. coli K-12 was a more effective biosorbent compared to the non-genetically modified E. coli K-12 (p< 0.05).